The Time Analysis of the Electronic Devices’ Restoration - Stupak, V. (Elektronika ir Elektrotechnika, 2004)
The restoration of electronic devices in the process of exploitation is analyzed. The devices’ maintainability index – a restorationmean time is regarded. The two components’ evaluation method of the given index is offered: an expectation mean time in the repairregime from the beginning of the restoration work and an expectation mean time in the repair regime of the necessary components forthe restoration work. The maintenance system in the repair regime is analyzed as well as the providing of the repair system with thenecessary components. A closed multi – channel queueing system with a finite waiting room is used as a model of the maintenancesystem. Analyzing the providing of the repair organ with the necessary components the two complement ways are regarded. An open (inthe first case) and a closed (in the second case) multi – channel queueing system with a finite waiting room are used as models forproviding a repair organ with the necessary components. The FIFO method of the requests’ service is used in all the analyzed systems ofthe mass cases. Ill. 3, bibl. 5 ( in Lithuanian; summaries in Lithuanian, English and Russian ).